Direct fabrication of Cd–In–S alloy quantum dots thin films. (16th October 2019) - Chen, Yanyan; Hu, Qi; Wang, Qiang; Yu, Minghui; Gong, Xiaoyu; Zha, Tianyong; Gao, Jingying; Li, Shenjie
Abstract: In this article, a new simple one-step process to fabricate Cd–In–S luminescent quantum dot thin films (QDTFs) is provided. Metal sulfide precursor solutions were manufactured by directly adding a certain amount of butylamine and carbon disulfide in the ethanol solution followed by dissolving Cd(OH)2 and In(OH)3 powder. Cd–In–S luminescent QDTFs can be obtained by mixing Cd and In precursor solutions and then spinning on a cover slip and annealing on a hot plate at 190 °C under air atmosphere directly without complicated synthesis method. By changing the sintering parameters including the temperature, time and ratios of (Cd+In)/ligand, the Cd–In–S luminescent QDTFs covering the entire visible light wavelength from 470 to 628 nm can be obtained. The Cd–In–S luminescent QDTFs exhibited remarkable optical properties and has potential application in solar cell and light emitting diode, with the photoluminescence quantum yield of up to 36.5% .